A patrimonialização do arquivo pessoal: análise dos registros Memória do Mundo do Brasil, da UNESCO - Duarte, Renato Crivelli [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
On the last decades the study with focus in personal records had been recurring in Brazil, which shows a growth in this thematic. Similarly, the concept of heritage has taken a central place in policy discussions related to the preservation worldwide. The development of studies on personal records shows the importance of these set of documents. Even sometimes seen as less important records, papers accumulated by a person have been increasingly recognized for their potential for representation of a historical period in society. This recognition is responsible to elevate its status within the government and scientific community, incising the concern to perseveration. On the heritage side, leads to the development of a broad sense related to the cultural and social status. Initially, only historical buddings and fine arts, preferentially religion related, where understood as part of the historical and cultural heritage especially in the Latin American reality. In present time, this sense was amplify drastically and new categories where created. Between these categories, surges the documental heritage. On concept less explored, responsible for more doubts and answers. Concern with this category, UNESCO, responsible for the coordination and developments of a series of preservation actions across the world, developed the Memory of World Program. This program has the objective to stimulate the preservation and access to records consider relevant for the mankind memory, as well to contribute to increase the status of this records. Brazil is a participant of this program and development since 2007 the selection of records holdings relevant for the cultural and national memory, which will integrated the Memory Of World Record. Between the years 2007 and 2010 a total of 38 holdings where nominated, 12 are personal... (Complete abstract click electronic access below)

Nas últimas décadas os estudos com foco nos arquivos pessoais têm sido recorrentes no Brasil, o que nos mostra um desenvolvimento desta temática. Do mesmo modo, o conceito de patrimônio tem tomado lugar central em discussões políticas relacionadas à sua preservação e ampliação em todo o mundo. O desenvolvimento dos estudos sobre arquivos pessoais afirmam as qualidades informativas históricas destes conjuntos documentais. Mesmo com seu estereótipo de papéis acumulados por uma pessoa, são cada vez mais reconhecidos seus potenciais de representação de um período histórico da sociedade. Este reconhecimento é responsável por elevar seu status junto à comunidade científica e governos, propiciando maior preocupação em preservá-los. Do lado do conceito de patrimônio, o seu desenvolvimento histórico, em consonância com os desenvolvimentos culturais e sociais, gerou uma ampliação de seu sentido. Inicialmente apenas obras arquitetônicas e obras de arte, preferencialmente religiosas, eram entendidas como patrimônio histórico e cultural. Atualmente, este sentido se ampliou drasticamente e muitas novas categorias patrimoniais foram incorporadas. Dentre estas categorias, surge a do patrimônio documental. Um conceito pouco explorado, responsável por gerar mais dúvidas do que respostas. Ciente desta categoria patrimonial, a UNESCO, responsável por desenvolver e coordenar uma série de ações preservacionistas em todo o mundo, desenvolveu o Programa Memória do Mundo. Este programa tem por objetivo estimular a preservação e o acesso a conjuntos documentais considerados relevantes para a memória da humanidade, bem como contribuir para o maior reconhecimento dos valores destes conjuntos. O Brasil é participante deste programa e desenvolve desde 2007 a seleção de conjuntos documentais...
Keywords: Documental heritage; Documentos; Patrimonio; Arquivos e arquivamento (Documentos); Arquivologia; Arquivos - Organização e Administração